Isolasi dan Identifikasi Bakteri Asam Laktat Dangke Asal Kabupaten Enrekang Sulawesi Selatan - Suhaeni S; Akhmad Syakur (Biogenesis: Jurnal Ilmiah Biologi, 2016)
The research conducted in Enrekang, South Sulawesi aims to obtain the isolates of lactic acid bacteria from dangke and identify the lactic acid bacteria that have potential as a probiotic. Identification included physical and microbiological test. The physical tests include pH and total titrated acid test, while Microbiological testing include morphological observation of bacterial colonies, gram staining and catalase test. The results showed 2 isolates with characteristics of lactic acid bacteria, positive gram, rounded and shaped. Catalase test on all isolates showed a negative result, no gas bubbles when reacted with H2O2. Thus it was concluded that all isolates shows the characteristics of lactic acid bacteria.